2006
DOI: 10.1002/humu.9444
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of theABCC6 gene and the proximalABCC6 gene promoter in German patients with pseudoxanthoma elasticum (PXE)

Abstract: Pseudoxanthoma elasticum (PXE) is a genetic disorder characterized by calcification of elastic fibers in dermal, ocular, and cardiovascular tissues. Recently, ABCC6 mutations were identified as causing PXE. In this follow-up study we report the investigation of 61German PXE patients from 53 families, hitherto the largest cohort of German PXE patients screened for the complete ABCC6 gene. In addition, we characterized the proximal ABCC6 promoter of PXE patients according to mutation. In this study we identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 47 publications
4
37
0
Order By: Relevance
“…Several transcription factors have been implicated later in the regulation of the human and mouse ABCC6 genes based on luciferase reporter gene experiments (15)(16)(17)(18)(19). More recently, it has been proposed, that the ABCC6 promoter polymorphisms may be functionally linked to PXE (20) and our results suggested that these polymorphisms are modulating the binding capacity of previously identified transcription factors (21). However, to date no cellular signaling pathway has been convincingly linked to the regulation of ABCC6 expression.…”
mentioning
confidence: 49%
“…Several transcription factors have been implicated later in the regulation of the human and mouse ABCC6 genes based on luciferase reporter gene experiments (15)(16)(17)(18)(19). More recently, it has been proposed, that the ABCC6 promoter polymorphisms may be functionally linked to PXE (20) and our results suggested that these polymorphisms are modulating the binding capacity of previously identified transcription factors (21). However, to date no cellular signaling pathway has been convincingly linked to the regulation of ABCC6 expression.…”
mentioning
confidence: 49%
“…mutation and mutational analysis of ABCC6 was performed as previously described. 6 Analysis of ABC Transporter Transcript Levels by TaqMan Low-Density Array Transcript levels for 47 human ABC transporters and the reference gene 18S rRNA were analyzed by a well-established real-time PCR-based TaqMan low-density array (TLDA), as described. 37 Total RNA was extracted from 1 Â 10 6 cells using the RNeasy Midi Kit (Qiagen, Hilden, Germany).…”
Section: Abcc6 Genotypingmentioning
confidence: 99%
“…Progressive calcification and fragmentation of elastic fibers are characteristic hallmarks of pseudoxanthoma elasticum (PXE), which is caused by mutations in the ABCC6 gene encoding the multidrug resistance-associated protein 6 (MRP6, [1][2][3][4][5][6]. Recently, two different abcc6 knockout mouse models were generated, that exhibited a PXE phenotype, strengthening ABCC6/MRP6 as the candidate gene for PXE.…”
mentioning
confidence: 99%
“…Genotype revealed a compound heterozygous mutation with different PXE-inducing mutations on each complementing allele (p.R1141X/c.3883-6G>A). Mutational analysis was performed by the cooperating Institute of Laboratory and Transfusion Medicine of the Heart and Diabetes Center North Rhine Westphalia of the Ruhr University of Bochum in context of previous research [5,6]. The Patient caught our attention due to a pathological decrease of anklebrachial-indices (ABI) after 5 minutes of exercise on the treadmill (12° inclination; 3.2 km/h) without a detectable correlate in color-coded duplex sonography.…”
Section: Case Presentationmentioning
confidence: 99%